Ta’tsīru Istikhdāmi Educaplay ‘alā an-Nasyāṭ at-Ta‘līmī wa ad-Darajāt fī Durūs al-Lughah al-‘Arabiyyah fī Ma‘had al-Hijrah - Anita Soba; Abu Darda; Mandrasi Amira Sa’idah; Azkia Ni’matul Maula; Sofia Amelia Rezeki (Al Maghazi : Arabic Language in Higher Education, 2026)
Arabic is one of the subjects taught in schools, especially in institutes. However, low student learning outcomes often become a major obstacle to achieving educational goals. One key reason is the limited use of engaging and interactive learning media that can create an effective learning environment. Therefore, innovative learning strategies are needed to encourage students’ active participation during the learning process. This study aimed to determine the effectiveness of using Educaplay in improving the learning outcomes of seventh-grade students at Al-Hijra Institute. The research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection. Data were collected through observations of student activities, interviews, and questionnaires to assess students’ perceptions of the learning process. The results revealed a significant improvement in students’ learning outcomes. Scores increased from 25% before the intervention to 42% in the first cycle and reached 83% in the second cycle. These findings indicate that Educaplay, with its interactive features, successfully made learning more engaging and enjoyable, while also enhancing students’ motivation and understanding of the material. Further research is recommended to examine the use of Educaplay in various Arabic language skills with a larger sample size and to compare it with other digital learning media in order to obtain more comprehensive results.